People with Hearing Loss: Effects of Reading Instruction on Vocal Verbal Repertoire - Almeida-Verdu, Ana Claudia Moreira [UNESP]; Lucchesi, Fernando Del Mando; Silva, Leandra Tabanez Nascimento (Springer Nature, 2023)
This chapter systematizes the main learning needs identified in children with hearing loss (HL) and cochlear implant (CI) and the common characteristics of the main programs for teaching auditory and verbal skills reported in the interdisciplinary literature. Considering the documented scarcity of intervention programs that incorporate the criteria of scientific evidence and the recommendation of the use of single-subject experimental design in research with this population, the contributions of Equivalence Based Instruction (EBI) are presented as a methodological proposal with technological potential in the study of the auditory rehabilitation process in children with CI and in the literacy stage. Based on the generative potential of EBI and the transfer of control of stimuli from pictures (naming) to textual stimuli (reading) on speech, already documented in listeners, the chapter proposes the study of an inverse direction: from the teaching oral reading stimulus control transfers from the textual stimulus to the figure, producing a more accurate speech in children with CI, in conditions that there are no textual cues to assist in controlling the accuracy of speech. It presents the synthesis of research conducted in the scope of the National Institute of Science and Technology, Studies on Behavior, Cognition and Teaching (Instituto Nacional de Ciência e Tecnologia, Estudos sobre Comportamento, Cognição e Ensino [INCT-ECCE]; from UNESP-USP-UFSCar universities) as an auxiliary technology in the rehabilitation process.
Keywords: Equivalence-based instruction; Hearing loss; Listening skills; Reading comprehension; Speech accuracy